2011
DOI: 10.1016/j.ajo.2011.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Dry Eye Syndrome in a United States Veterans Affairs Population

Abstract: PURPOSE To evaluate the prevalence of dry eye syndrome (DES) and its associated risk factors in a US Veterans Affairs population receiving ocular care services. DESIGN Retrospective study. METHODS SETTINGS Patients were seen in the Miami and Broward Veterans Affairs eye clinics between 2005 and 2010. PATIENTS POPULATION Patients were divided into cases and controls with regard to their dry eye status (cases = ICD9 code for DES plus dry eye therapy; controls = patients without ICD9 code plus no therapy).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
143
4
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(169 citation statements)
references
References 30 publications
15
143
4
7
Order By: Relevance
“…This agrees with previous studies in which DED had a negative effect on mental health (Mertzanis et al 2005;Galor et al 2011;Kim et al 2011;Le et al 2012;Li et al 2012;Wang et al 2012;Sakane et al 2013). The study on a non-clinic-based population in China showed lower QOL for mental health in subjects with DED (Le et al 2012).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This agrees with previous studies in which DED had a negative effect on mental health (Mertzanis et al 2005;Galor et al 2011;Kim et al 2011;Le et al 2012;Li et al 2012;Wang et al 2012;Sakane et al 2013). The study on a non-clinic-based population in China showed lower QOL for mental health in subjects with DED (Le et al 2012).…”
Section: Discussionsupporting
confidence: 82%
“…However, to the best of our knowledge, no study has ever examined the relationship between DED and QOL in non-clinic-based subjects in Japan, whereas DED has been reported to be related to poor QOL and depression in a general population in other countries (Galor et al 2011;Le et al 2012;Wang et al 2012). The major purpose of the present study is, therefore, clarify the relationship between DED and QOL in non-clinic-based Japanese subjects.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Araki et al reported a significantly positive relationship between eye discomfort and depression in only females [26]. Another study has been shown that dry eye was observed almost twice as often in individuals with mental illness, such as depression and PTSD, as those without [34]. On the other hand, Zhaoji et al have described that there was no relationship between eye strain and the GHQ-12 score in females who use VDT [22].…”
Section: Discussionmentioning
confidence: 99%
“…4 It is also one of the main reasons for seeking eye care among older people because its overall risk raises by 1.06 for each increased decade. 5 Sjögren syndrome (SS) is a chronic systemic autoimmune disease characterized by lymphocytic infiltration of the exocrine glands and mucosal epithelia, resulting in dry eye as well as dry mouth. 6 This condition causes one of the most severe types of dry eye disease; the prevalence of its primary type varies greatly, from 0.09% to 2.7% depending on the diagnostic criteria used.…”
Section: Introductionmentioning
confidence: 99%